Effect of aeration and hydraulic loading rate on nitrogen removal by subsurface infiltration systems. (19th February 2019) - Zheng, Fanping; Huang, Linli; Pan, Jing; Qi, Shiyue; Tan, Chaoquan; Xiao, Lu
Abstract: This study investigated the effect of hydraulic loading rate (HLR) on matrix dissolved oxygen (DO), organic matter removal, nitrogen removal, N2 O emissions, and the abundances of functional genes participating in nitrogen removal in intermittent aerated mode (IAM) and nonaerated mode (NAM) subsurface infiltration systems (SISs). In contrast to NAM SISs, IAM SISs were able to create aerobic conditions in the upper matrix (above 50 cm depth) and anoxic or anaerobic conditions in the lower matrix (below 80 cm depth). Subsequently, this enhanced the abundance of functional genes related to nitrogen removal. Chemical oxygen demand (COD) and nitrogen removal performance were significantly higher under IAM SISs than with NAM SISs. Under a HLR of 0.3 m 3 /(m 2 d), the IAM SIS was able to achieve low N2 O emissions (12.6 mg/[m 2 d]) along with removal efficiencies of 90.5%, 91.4%, and 85.7% for COD, ammonia nitrogen ( NH 4 + ‐N), and total nitrogen (TN), respectively. Practitioner points: Intermittent aeration successfully realized sequential aerobic and anaerobic conditions at 50 cm depth and at 80 and 110 cm depths of a subsurface infiltration system. Intermittent aeration reduced N2 O emissions and improved hydraulic loading rate and organic matter, nitrogen removal efficiencies. Intermittent aeration enhanced the abundances of amoA, nxrA, napA, narG, nirS, nirK, qnorB, and nosZ.